Combination of hepatocyte fraction and diffusion-weighted imaging as a predictor in quantitative hepatic fibrosis evaluation. - Cui, Enming; Li, Qing; Wu, Juanhua; Mei, Yingjie; Yu, Juan; Long, Wansheng; Li, Zhuoyong; Lan, Yong; Lin, Fan (Abdominal Radiology, 2020)
Objective: To investigate the performance of the combined hepatocyte fraction (HepF) and apparent diffusion coefficient (ADC) values to stage hepatic fibrosis (HF) in patients with hepatitis B/C. Materials and methods: A total of 281 patients with hepatitis B/C prospectively underwent gadoxetate disodium-based T1 mapping and diffusion-weighted imaging. HepF was determined from pre and postcontrast T1 mapping with pharmacokinetics. The independent predictors of the HF stage (S0–4) were identified from HepF, ADC, conventional T1-based parameters, and age using a logistic regression analysis. The performances of independent and combined predictors in diagnosing various HF stages were compared by analyzing receiver operating characteristic curves. The intraclass correlation coefficient (ICC) was used to assess the interobserver reproducibility of each predictor. Results: In total, 167 patients with various stages of HF were included. All measurements had excellent interobserver agreement (ICC ≥ 0.75). The hepatic relative enhancement, HepF ,and ADC values were significantly different among various HF stages (p < 0.05). The HepF and ADC were independent predictors of > S0, > S1, > S2 , and > S3 disease (p < 0.05). T1Liver, T1Spleen, and T1Liver/Spleen were independent predictors of S > 2 disease (p < 0.05). The performance of HepF combined with the ADC (area under the curve (AUC) = 0.84–0.95) was higher than HepF (AUC = 0.79–0.92) or ADC (AUC = 0.82–0.89) alone in diagnosing > S0, > S1, > S2 , and > S3 disease. Conclusion: The combined predictor of HepF and ADC shows acceptable performance for staging HF.